Confocal analysis of the penetrability of the AH Plus sealer after retreatment procedure with rotary or reciprocating systems followed by two additional cleaning methods. - Martins, Milena Perraro; Cavenago , Bruno Cavalini; Da Silveira Bueno, Carlos Eduardo; De Martin, Alexandre Sigrist; Kato , Augusto Shoji; Vivan , Rodrigo Ricci; Hungaro Duarte , Marco Antonio (Iranian Endodontic Journal, 2022)
Introduction: The aim of this study was to evaluate the AH Plus sealer penetration into dentinal tubules after root canal retreatment followed by two additional cleaning methods. Methods and Materials: Thirty-two mandibular premolars with single canal were prepared up to the F4 ProTaper Universal instrument and filled by a single cone technique with the addition of Rhodamine B dye to Endofill sealer. For the retreatment procedure, the teeth were randomly divided into four experimental groups (n=8) as follows: Reciproc R40 with ultrasonic activation (RU), Reciproc R40 with sonic agitation (RS), ProTaper Next until X4 instrument with ultrasonic activation (PTNU), and ProTaper Next (X4) with sonic activation (PTNS). A new root canal filling was done using a System B technique, and the AH Plus sealer was mixed with Fluorescein dye. The roots were axial sectioned at 3, 5, and 7 mm from the apex and were assessed by a confocal laser scanning microscopy using the method of epifluorescence with wavelengths of absorption and emission for rhodamine B and fluorescein. In the obtained images, the sealer penetration into the dentinal tubules was evaluated. The data were converted into percentages and submitted to Mann-Whitney and Kruskal-Wallis followed by Dunn’s tests (P<0.05). Results: In all groups were found penetration of the AH Plus into the dentinal tubules. Statistical difference was found (P<0.05) in the ProTaper Next groups in relation the Reciproc groups for 3 mm root canal level regardless of additional cleaning method used. For the other sections the sealer penetration was similar (P>0.05) for all groups. Conclusion: Based on this ex vivo study the retreatment with ProTaper Next showed significantly greater penetration of AH Plus sealer into dentinal tubules in the apical third. The additional cleaning methods did not improve the removal of filling material in all sections evaluated.